Electrocardiogram Parameters That Affect the Success Rate of Radiofrequency Ablation in Patients with Outflow Tract Ventricular Premature Complexes - Zhen Ye; Zhe Xu; Kezeng Gong; Xuehai Chen; Weiwei Wang; Jianhua Chen; Lianglong Chen; Feilong Zhang (Cardiovascular Therapeutics)
Objectives. The objectives of this study are to assess the efficacy of radiofrequency catheter ablation (RFCA) in patients with outflow tract (OT) ventricular premature complexes (VPCs) and to explore the electrocardiographic (ECG) features of initially successful procedures. Methods. Based on the outcome of ablation, 154 consecutive patients with OT-VPCs who underwent RFCA from January 2017 to December 2019 were divided into two groups. The rate of successful procedures and the ECG features were analyzed and compared between the two groups. Results. The highest success rate was found in patients with VPCs from the right ventricular outflow tract (RVOT), and the lowest success rate was evident among patients with complexes from both the RVOT and the left ventricular OT (LVOT). The patients with successful procedures (136) reflected a lower pseudo delta wave ratio (16.2% vs. 44.4%, P<0.01), a smaller R-wave amplitude in lead V1 (V1) (0.23±0.24 mV vs. 0.35±0.44 mV, P<0.05), shorter intrinsicoid deflection time in lead V2 (V2) (44.00±18.33 ms vs. 57.41±20.67 ms, P<0.01), a shorter RS duration in V2 (93.67±21.33 ms vs. 106.93±18.76 ms, P<0.01), and smaller R/S-waveratios in V2. Furthermore, multivariate analysis demonstrated that RS duration in V2 was above 109.17 ms and R/S ratio in V2 was above 0.28, forecasting a failed procedure. Conclusions. The ECG predictors of failed ablation were characterized by RS duration and R/S ratio in V2.